2023
DOI: 10.3389/fphar.2023.1280559
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Panax notoginseng saponins (Xuesaitong) for patients with acute ischemic stroke: a systematic review and meta-analysis of randomized controlled trials

Xinyi Shi,
Luda Feng,
Yixuan Li
et al.

Abstract: Background: Stroke is the major cause of mortality and permanent disability and is associated with an astonishing economic burden worldwide. In the past few decades, accumulated evidence has indicated that Xuesaitong (XST) has therapeutic benefits in cases of acute ischemic stroke (AIS). Our study aimed to provide the best current body of evidence of the efficacy and safety of XST for patients with AIS.Methods: This is a systematic review and meta-analysis of randomized controlled trials (RCTs). We searched ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…This study indicated that in comparison to other outcome indicators, authors of previous studies appeared to prefer to use the total efficiency rate rather than all-cause mortality as an endpoint indicator. And a few studies hold a dialectical perspective toward this phenomenon ( Shi et al, 2023 ). This is due to the fact that the total efficiency rate, as a composite indicator, still lacks a universally accepted standardized evaluation method, and it is an insufficient strategy to evaluate a composite endpoint as if it were a sole primary endpoint ( McCoy, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study indicated that in comparison to other outcome indicators, authors of previous studies appeared to prefer to use the total efficiency rate rather than all-cause mortality as an endpoint indicator. And a few studies hold a dialectical perspective toward this phenomenon ( Shi et al, 2023 ). This is due to the fact that the total efficiency rate, as a composite indicator, still lacks a universally accepted standardized evaluation method, and it is an insufficient strategy to evaluate a composite endpoint as if it were a sole primary endpoint ( McCoy, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Panax notoginseng (Burkill) F.H.Chen [Araliaceae; Notoginseng radix et rhizoma ] is a medicinal plant widely used in China. Traditional Chinese medicine has found that it simultaneously possesses the functions of promoting blood circulation and stopping bleeding, and it is widely used in various conditions involving blood stasis and bleeding disorders ( Shi et al, 2023 ; Wu et al, 2023 ). Panax notoginseng saponins (PNS) are the main bioactive metabolites of P. notoginseng , and their primary chemical metabolites include five types of dammarane-type saponins, namely, notoginsenoside R1, ginsenoside Rg1, ginsenoside Re, ginsenoside Rb1, and ginsenoside Rd ( Sun et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the main clinical formulation of PNS, P. notoginseng saponins injections (PNSI, including Xuesaitong injection and Xueshuantong injection) have undergone several clinical trials and systematic reviews, indicating theirs ability to reduce the occurrence of disabilities and improve neurological deficits as well as activity of daily living ( Dai et al, 2022 ; Shi et al, 2023 ). However, it is crucial to note that whether AIS patients have received or not received IVT has a significant difference on their prognosis and medication ( National Institute of Neurological Disorders and Stroke rt-PA Stroke Study Group, 1995 ), and existing systematic reviews have not yet made a distinction among participants on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…As the main clinical formulation of PNS, P. notoginseng saponins injections (PNSI, including Xuesaitong injection and Xueshuantong injection) have undergone several clinical trials and systematic reviews, indicating theirs ability to reduce the occurrence of disabilities and improve neurological deficits as well as activity of daily living (Dai et al, 2022;Shi et al, 2023). However, it is crucial to note that whether AIS patients have received or not received IVT has a significant difference on their prognosis and medication (National Institute of Neurological Disorders and Stroke rt-PA Stroke Study Group, 1995), and existing systematic reviews have not yet made a distinction among participants on this issue.…”
Section: Introductionmentioning
confidence: 99%